The Failure of Schools under Covid-19 Policies in Germany – what it means and how it could happen. A social-hermeneutical ethics perspective - Döring, Ole (Władza Sądzenia, 2021)
This essay describes the impact of COVID-19 related policies on the democratic fabric of German society, focusing the situation of children. It applies a methodology of ethics for salutogenesis, exploring, how policies and underlying motifs align with doing the right things for the right reasons. Five key areas are analyzed in the social-political specter of power of health-related judgement, connecting psychology, politics, economy, academia and culture. The discussion finds that the crisis reveals grave and basic flaws in the texture of democratic culture that could be healed by serious measures to reinvigorate the spirit of the German Constitution.